Challenging the elite-public divide; Representing former Indonesian first lady, Ani Yudhoyono in online news discourse - Ahlstrand, Jane Louise (UI Scholars Hub, 2023)
Women in politics invariably attract heightened levels of attention due to their marked difference to the masculine political norm. With the rise of social media and online news, political women can achieve visibility, but also experience even more intense scrutiny. Former first lady, Ani Yudhoyono became an iconic figure in the lead up to the 2014 Indonesian presidential election, through her association with her husband’s flailing presidency, and as a high-profile political woman involved in social media blunders. Using critical discourse analysis, specifically social actor analysis, this paper examines the discursive strategies engaged by the mainstream Indonesian online news media to malign Ani Yudhoyono, and draw a wedge between her and the Indonesian public, which in turn undermined her husband’s presidency. The analysis highlights the role of online news media discourse in shaping power relations and ideological groupings, as well as the role of first lady as a target of political contestation.